2022
DOI: 10.1111/all.15404
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal antibiotic exposure, asthma, and the atopic march: A systematic review and meta‐analysis

Abstract: Antibiotic use during pregnancy may increase the risk for asthma in children. We performed a meta-analysis assessing prenatal antibiotic exposure and the risk for childhood wheeze or asthma, as well as for diseases associated with the atopic march.A systematic literature search protocol (PROSPERO-ID: CRD42020191940) was registered and searches were completed using Medline, Proquest, Embase, and the Cochrane central register of controlled trials. Screening for inclusion criteria: published in English, German, F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 70 publications
(111 reference statements)
1
14
0
Order By: Relevance
“…Finally, we were not able to analyze the effect of prenatal antibiotics on AD by types of antibiotic use, which may have influenced the risk in patients with asthma. 10,11 However, to our knowledge, this effect did not exist when investigating the influence of antibiotic exposure during pregnancy on offspring AD. 9,20,24,33 In conclusion, this cohort study revealed that maternal antibiotic use during pregnancy was associated with a slightly increased risk of childhood AD.…”
Section: Strengths and Limitationsmentioning
confidence: 75%
“…Finally, we were not able to analyze the effect of prenatal antibiotics on AD by types of antibiotic use, which may have influenced the risk in patients with asthma. 10,11 However, to our knowledge, this effect did not exist when investigating the influence of antibiotic exposure during pregnancy on offspring AD. 9,20,24,33 In conclusion, this cohort study revealed that maternal antibiotic use during pregnancy was associated with a slightly increased risk of childhood AD.…”
Section: Strengths and Limitationsmentioning
confidence: 75%
“…A meta-analysis [ 12 ] also showed that early respiratory tract infection within 2 years old was associated with the development of asthma in school-age children. It has been demonstrated in numerous studies that maternal adverse exposure during pregnancy, such as passive smoking [ 39 ], diet [ 40 ], psychological status [ 41 ], pregnancy complications [ 42 ], and antibiotic exposure during pregnancy [ 43 ], was associated with a greater likelihood of AR in offspring. Additionally, studies have provided compelling evidence that adverse exposures in the early postnatal period, such as antibiotic use [ 13 ], pet exposure [ 44 ] and air pollution [ 45 ], may increase the risk of a child developing allergies.…”
Section: Discussionmentioning
confidence: 99%
“…8 Three subsequent meta-analysis showed a positive association. [9][10][11] In a study by Cait et al, the risk of eczema/dermatitis was increased in their pooled data (RR 1.28; 95% CI: 1.06-1.53). However, high heterogeneity among the data was also mentioned by the authors.…”
Section: Introductionmentioning
confidence: 92%
“…The pooled odds ratio (OR), which was 1.3 (95% CI: 0.86–1.95), indicated there was no association, although the estimate was elevated 8 . Three subsequent meta‐analysis showed a positive association 9–11 . In a study by Cait et al, the risk of eczema/dermatitis was increased in their pooled data (RR 1.28; 95% CI: 1.06–1.53).…”
Section: Introductionmentioning
confidence: 99%